Analisis Politik Media Sosial Terhadap Demokrasi Di Indonesia Menurut Perspektif Siyasah - Yusmila; Kusuma, Sintia Wati; Fathona, Cici; Lubis, Mhd Alfath; Nasution, Achmad Ramadhan (Tabayyun : Journal Of Islamic Studies, 2023)
This article was written in order to find out more deeply about the influence of social media on democracy from a religious perspective. This analysis can help understand how social media can influence democratic processes and how this influence can be managed to ensure that social media contributes to strengthening democracy. This article concludes that in Islam there are guidelines and values that must be followed to disseminate information, including in political matters. You can express yourself on social media, but it must be within the framework of sharia.